2021
DOI: 10.1155/2021/6668463
|View full text |Cite
|
Sign up to set email alerts
|

Ligase Pellino3 Regulates Macrophage Action and Survival in Response to VSV Infection in RIG‐I‐Dependent Path

Abstract: Sensing of viral particles and elements that initiate mechanisms of immune response is an intrinsic ability of mammalian cells. Regulatory cytokines and antiviral mediators are released after triggering of complex signaling cascades in response to interaction of pathogen particles with pattern recognition receptors (PRRs) leading to the production of interferons (IFN) and proinflammatory cytokines. Viral RNA in the cytoplasm constitute a potent danger molecule that recognition is performed by RIG-I-like recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 34 publications
1
11
1
Order By: Relevance
“…Our previous studies have shown that during VSV infection, viral particles replicate in Pellino3-knockout macrophages cell line more effectively than in wild-type cells. Increased viral replication resulting in cell lysis and death was aided by impaired synthesis of type I IFN and inflammatory cytokines production as a consequence of disturbances in the ERK1/2 pathway regulation [ 22 ]. To elucidate the role of Pellino3 in IFN-I-dependent signaling pathways, we created the THP-1 cell line with PELI3 gene knockout ( PELI3 −/− ) using the CRISPR/Cas9 technique.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous studies have shown that during VSV infection, viral particles replicate in Pellino3-knockout macrophages cell line more effectively than in wild-type cells. Increased viral replication resulting in cell lysis and death was aided by impaired synthesis of type I IFN and inflammatory cytokines production as a consequence of disturbances in the ERK1/2 pathway regulation [ 22 ]. To elucidate the role of Pellino3 in IFN-I-dependent signaling pathways, we created the THP-1 cell line with PELI3 gene knockout ( PELI3 −/− ) using the CRISPR/Cas9 technique.…”
Section: Resultsmentioning
confidence: 99%
“…Pellino3-regulated signaling pathways have been previously related to MAP kinase pathways [ 22 , 23 ]. Therefore, in the next step, we decided to examine the activation of MAPK kinases: ERK1/2 and p38.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations